2007
DOI: 10.1016/j.chroma.2006.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for prediction of peptide retention time in reversed-phase high-performance liquid chromatography: Hydrophilicity/hydrophobicity of side-chains at the N- and C-termini of peptides are dramatically affected by the end-groups and location

Abstract: The value of reversed-phase high-performance liquid chromatography (RP-HPLC) and the field of proteomics would be greatly enhanced by accurate prediction of retention times of peptides of known composition. The present study investigates the hydrophilicity/hydrophobicity of amino acid sidechains at the N-and C-termini of peptides while varying the functional end-groups at the termini. We substituted all 20 naturally occurring amino acids at the N-and C-termini of a model peptide sequence, where the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 41 publications
6
80
0
4
Order By: Relevance
“…This observation is consistent with previous observations for small molecules [3], indicating that lipophilicity is a general property that affects permeability. Analysis of surface properties of simulated structures revealed that the retention times were also related to the surface hydrophobicity of the cyclic peptides ( Figure 6), which is consistent with studies on linear peptides and their retention times [37]. This correlation suggests that the total surface area of exposed hydrophobic atoms/residues is related to peptide lipophilicity and affects peptide permeability.…”
Section: Discussionsupporting
confidence: 72%
“…This observation is consistent with previous observations for small molecules [3], indicating that lipophilicity is a general property that affects permeability. Analysis of surface properties of simulated structures revealed that the retention times were also related to the surface hydrophobicity of the cyclic peptides ( Figure 6), which is consistent with studies on linear peptides and their retention times [37]. This correlation suggests that the total surface area of exposed hydrophobic atoms/residues is related to peptide lipophilicity and affects peptide permeability.…”
Section: Discussionsupporting
confidence: 72%
“…It was based on the amino acid location within a peptide and its impact on peptide apparent hydrophobicity. Previous studies have also highlighted the impact of N-and C-terminal amino acids on the retention time of peptides in RP conditions (Krokhin, 2006;Tripet et al, 2007). These studies showed a similar trend to the model herein concerning the influence of each residue on peptide hydrophobicity with W, F, L and I having the highest impact.…”
Section: Accepted M Manuscriptsupporting
confidence: 69%
“…This is the case for chromatographic separation as peptide retention on a chromatographic matrix depends both on the sequence and the chromatographic conditions (Zou, Zhang, Hong, & Lu, 1992). The retention time of short peptides can be predicted using algorithm models based on properties such as peptide size and amino acid position within the peptide sequence (i.e., at the N-, the C-terminus or within the peptide sequence) (Krokhin, 2006;Le Maux, Nongonierma, & FitzGerald, 2015;Meek, 1980;Tripet et al, 2007). Furthermore, the combination of different separation modes such as hydrophilic interaction liquid chromatography (HILIC) and reverse-phase (RP) chromatography has been shown to further enhance the accuracy of short peptide identification (Harscoat-Schiavo et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…5B) closely matches (i) the pattern obtained when they were purified from a venom sample (13) and (ii) the predicted behavior based on differences in amino acid sequence using the method of Tripet et al (19) (data not shown). Based on these results we believe it is reasonable to conclude that in addition to ␦-CnVID, ␦-CnVIB and ␦-CnVIC are authentically folded.…”
Section: Purification Of 3 Novel ␦-Conotoxins From Crude Venom-supporting
confidence: 56%